PENGGUNAAN SERBUK ARANG AKTIF BIJI KELOR UNTUK MENURUNKAN KADAR NITRIT DALAM AIR - Ana Hidayati Mukaromah; Rusda Abja; Fandhi Adi Wardoyo (Eksergi, 2020)
Nitrite (NO2 - ) is a compound that can distrupting oxyhaemoglobin process and causes body weakness, fatigue, and samnolen. Either to reduce nitrite value in the water is to use activated charcoal moringa seeds, because it countains 4-alfa-L-rhamnosyloxy-benzilisothiocyanate substances. This research aims to find out influence of activated charcoal concentrate and immersion time variant to the reduction of nitrites ion in the water. Research object was nitrite ion in 10 ppm concentrate, the immersion with activated charcoal moringa seeds with concentrate variant 9 ; 12 ; and 15%w/v, with 10 ; 20 ; and 30 minutes immersion time. Nitrite assay performed with specfotometry methods with griess reagent. From the research results, optimum wave length is 540 nm and time stability of initial nitrite value 10 minutes with initial 4,7794 ppm. Reduction lowest nitrite value in the water is 9%w/v concentrate in 10 minutes time, with the result 3,1816 ppm and highest nitrite value is 15%w/v concentrate (1,1862 ppm). So that, can be conclude there is reaction activated charcoal moringa seeds variant concentration and immersion time to reducting nitrite ions in the water.